Book Review: RECEPTION OF WAR. A.S. bradford) war. antiquity and its legacy. pp. xvi + 176, maps. new york: oxford university press, 2015. cased. ISBN: 978-0-19-538090-3 (978-0-19-538091-0 pbk). - Nakamura, Byron (Classical Review, 2016)
Keywords: book.review; dept.his

Sabbatical leave report: Fall 2013 - Nakamura, Byron (Distribution: Fall 2013 ; History., 2013)
This leave was devoted to research and revision of two conference papers submitted for publication, and to revision of a book chapter on boxing in the antiquity The chapter was submitted and accepted for publication in the Cambridge Companion to Boxing series.
Keywords: dept.his; faculty_collection; sabbatical_report

Dreams of antiquity: H. P. Lovecraft’s great Roman dream of 1927 - Nakamura, Byron (Lovecraftian Proceedings No. 2, 2017)
This second volume of Lovecraftian Proceedings contains a wealth of cutting-edge scholarship on the dreamer from Providence, including substantial articles from both recipients of the S. T. Joshi Endowed Research Fellowship for H. P. Lovecraft at Brown University.  Lovecraftian Proceedings fosters exploration of Lovecraft as a rationalist who created an elaborate cosmic mythology, and how this mythology was influenced by, and has come to influence, numerous other authors and artists. The papers which comprise Lovecraftian Proceedings were presented during a key part of the NecronomiCon Providence convention, the Dr. Henry Armitage Memorial Symposium. TABLE OF CONTENTS Introduction             Dennis P. Quinn Dreams of Antiquity:  H. P. Lovecraft's Great Roman Dream of 1927Byron Nakamura The Poet’s Nightmare: The Nature of Things According to LovecraftSean Moreland Reordering the Universe: H. P. Lovecraft’s Subversion of the Biblical DivineRené J. Weise Resisting Cthulhu:  Milton and Lovecraft’s Errand in the Wilderness Marcello Ricciardi “The Discriminating Urban Landscapist": Tradition and Innovation in the Architectural Writings of H. P. LovecraftConnor Pitetti Tentacles in the Madhouse: The Role of the Asylum in the Fiction of H. P. LovecraftTroy Rondinone Unspeakable Languages: Lovecraft Editions in Spanish Juan L. Pérez-de-Luque Color out of Mind: Correlating the Cthulhu Mythos Universe to the Autism Disorder SpectrumLars G. Backstrom Darwin and the Deep Ones: Anthropological Anxiety in "The Shadow over Innsmouth" and Other StoriesJeffrey Shanks The “Inside” of H. P. Lovecraft’s Supernatural Horror in the Visual Arts Nathaniel R. Wallace H. P. Lovecraft’s OptimismMatthew Beach Insider, Outsider: From the Commonplace to the Uncanny in H. P. Lovecraft’s Narration and DescriptionsDaphnée Tasia Bourdages-Athanassiou H. P. Lovecraft, Georges Bataille, and the Fascination of the Formless: One Crawling Chaos Seen Emerging from Opposite ShoresChristian Roy  Ripples from Carcosa: H. P. Lovecraft, True Detective, and the Artist-InvestigatorHeather Poirier Lovecraft for the Little Ones: ParaNorman, Plushies, and MoreFaye Ringel and Jenna Randall Contributors AppendixAbstracts of Papers Presented at the Dr. Henry Armitage Memorial Scholarship Symposium,NecronomiCon Providence 20-23 August, 2015Chair: Dennis P. Quinn Index
Keywords: dept.his

Boxing in the ancient world - Nakamura, Byron J. (The Cambridge Companion to Boxing, 2019)
Keywords: dept.his